Considering people in systematic conservation planning: insights from land system science. Issue 7 (12th June 2018) - Iwamura, Takuya; le Polain de Waroux, Yann; Mascia, Michael B
Abstract : Species and ecosystems worldwide continue to decline and disappear in spite of decades of investment in conservation efforts. Systematic conservation planning (SCP) is a field of study designed to improve conservation programs by identifying land configurations that, if protected, would most efficiently sustain biodiversity. Despite contributing to species persistence in landscapes, SCP has been criticized for replacing site‐based conservation plans that often consider social context. In contrast, land system science (LSS), an emerging field that explores the process of land‐use and land‐cover change, integrates social systems and processes into conservation analyses. We suggest that by incorporating insights from LSS on social processes (eg livelihood adaptation or agricultural intensification), SCP can enhance the legitimacy of conservation plans, thereby reducing the gap between conservation planning and implementation. This represents a necessary first step for SCP to reinvent itself as a decision‐support tool that helps to reconcile the long‐standing divide between landscape‐level species conservation and social needs.